Absolute and relative training load and its relation to fatigue in football - Zurutuza, U.; Castellano, J.; Echeazarra, I.; Casamichana, D. (Frontiers in Psychology, 2017)
The aim of the study was to assess the relationship of external and internal training load (TL) indicators with the objective and subjective fatigue experienced by 15 semi-professional football players, over eight complete weeks of the competition period in the 2015-2016 season, which covered microcycles from 34th to 41st. The maximum heart rate (HRmax) and maximum speed (Vmax) of all the players were previously measured in specific tests. The TL was monitored via questionnaires on rating of perceived exertion (RPE), pulsometers and GPS devices, registering the variables: total distance (TD), player load 2D (PL2D), TD at >80% of the Vmax (TD80), TD in deceleration at < -2 m·sec-2 (TDD <-2), TD in acceleration >2 m·sec-2 (TDA >2), Edwards (ED), time spent at between 50 and 80% (50-80% HRmax), 80-90% (80-90% HRmax), and >90% of the HRmax (>90% HRmax), and RPE both respiratory/thoracic (RPEres) and leg/muscular (RPEmus). All the variables were analyzed taking into account both the absolute values accumulated over the week and the normalized values in relation to individual mean competition values. Neuromuscular fatigue was measured objectively using the countermovement jump test and subjectively via the Total Quality Recovery (TQR) scale questionnaire. Analytical correlation techniques were later applied within the general linear model. There is a correlation between the fatigue experienced by the player, assessed objectively and subjectively, and the load accumulated over the week, this being assessed in absolute and relative terms. Specifically, the load relative to competition correlated with the physical variables TD (-0.279), PL2D (-0.272), TDD < -2 (-0.294), TDA >2 (-0.309), and sRPEmus (-0.287). The variables related to heart rate produced a higher correlation with TQR. There is a correlation between objectively and subjectively assessed fatigue and the accumulated TL of a player over the week, with a higher sensitivity being shown when compared to the values related to the demands of competition. Monitoring load and assessing fatigue, we are closer to knowing what the prescription of an adequate dose of training should be in order for a player to be as fresh as possible and in top condition for a match. Normalizing training demands with respect to competition could be an appropriate strategy for individualizing player TL.